ANALISIS NILAI KARAKTER DALAM CERITA DONGENG PADA SISWA KELAS RENDAH SEKOLAH DASAR - Fathurohman, Irfai (Lentera: Jurnal Ilmiah Kependidikan, 2020)
This research to find out the value of character delivered by the high grade high school precursor nu holy whe high paying for this study for the procpectif case. The study described the value of the character in the fairy tales delivered by the second -grade high school seniors Muslimat NU holy. Data collection techniques documenting interviews, taking notes. Research shows that during high-value practice, from 18 character value indicators, lower-class students only instill 10 good values in the form of discipline, the value of hard work , the value of creative values, the value of social concern, the value of democracy, the value of tolerance, the value peace, religious values, the value of achievement,and pry value.